Implementation of a biochemical, clinical, and genetic screening programme for familial hypercholesterolemia in 26 centres in Spain: The ARIAN study - Arrobas Velilla, Teresa; Brea, Ángel; Valdivielso, Pedro (Frontiers in Genetics, 2022)
Background: Familial hypercholesterolemia (FH) is clearly underdiagnosed and undertreated. The aim of this present study is to assess the benefits of FH screening through a joint national program implemented between clinical laboratories and lipid units. Methods: All clinical laboratory tests from January 1, 2017 to December 31, 2018 were re-viewed, and those with LDL cholesterol (LDL-C) levels > 250 mg/dL were identified in subjects > 18 years of age of both sexes. Once secondary causes had been ruled out, the treating physician was contacted and advised to refer the patient to an LU to perform the Dutch Lipid Clinic Network score and to request genetic testing if the score was ≥ 6 points. Results: Of the 3,827,513 patients analyzed in 25 centers, 6,765 had LDL-C levels > 250 mg/dL. Having ruled out secondary causes and known cases of FH, 3,015 subjects were included, although only 1,205 treating physicians could be contacted. 635 patients were re-ferred to an LU and genetic testing was requested for 153 of them. This resulted in a finding of sixty-seven pathogenic variants for FH, most of them in the LDLR gene. Conclusions: Despite its limitations, systematic collaboration between clinical laboratories and lipid units allows for the identification of large numbers of patients with a phenotypic or genetic diagnosis of FH, which will reduce their vascular risk. This activity should be part of the clinical routine